Penjaminan Mutu Raudhatul Athfal dan Pendidikan Islam Anak Usia Dini di Indonesia: Tinjauan Sistematis Standar, Kepemimpinan, dan Implementasi - Agus Suprijanto; Sri Purwanti Nasution (WISE Pendidikan Indonesia, 2026)
Quality assurance in Raudhatul Athfal (RA) and Islamic early childhood education (PIAUD) institutions in Indonesia has become increasingly urgent because these institutions must align child development, Islamic values, national standards, accreditation requirements, and institutional leadership. However, studies on RA/PIAUD quality remain fragmented, often discussing standards, leadership, evaluation, accreditation, and implementation barriers separately. This systematic literature review synthesizes Indonesian studies published between 2019 and 2025 on quality assurance in RA and PIAUD institutions, focusing on standards, leadership, and implementation. The review followed PRISMA 2020 reporting guidance and PRISMA-S principles for transparent search reporting. Searches were conducted in Scopus, Web of Science, Google Scholar, Garuda, and Neliti using Indonesian and English keywords related to RA, PIAUD, Islamic early childhood education, quality assurance, accreditation, leadership, standards, and evaluation. From 202 records initially identified, 18 studies met the eligibility criteria and were included in the qualitative thematic synthesis. The synthesis indicates that quality assurance research in RA/PIAUD is dominated by three interrelated themes: fulfillment of national standards and accreditation, leadership and educator professionalism, and implementation constraints in learning evaluation, infrastructure, financing, and stakeholder participation. Most studies are local, descriptive, and institution-specific, with limited comparative, longitudinal, or mixed-method evidence. The article contributes a thematic map of RA/PIAUD quality assurance and highlights the need for integrated models connecting policy standards, leadership practices, and classroom-level quality improvement.